Analisis Representasi Estetika Tubuh dalam Film Imperfect: Karier, Cinta & Timbangan melalui Perspektif Teori Perbandingan Sosial (International Forum of Researchers and Lecturers, 2025)
Imperfect: Career, Love & Scales is a work that discusses the issue of body shaming and social pressure on beauty standards. Through a qualitative approach with social comparison theory analysis, this study reveals how the representation of body aesthetics is displayed in the film. The main character, Rara, experiences pressure to meet ideal beauty standards, such as a slim body and white skin, both in her work environment and family. This phenomenon reflects social construction and popular culture that reinforces beauty stereotypes. The impacts of this pressure include decreased self-esteem, anxiety, and unhealthy dieting behavior. This study shows that media-promoted beauty standards have a negative impact on individual mental health and encourage appearance-based discrimination. The film also critiques narrow beauty standards while conveying important messages about self-acceptance and diversity.